2009
DOI: 10.1111/j.1365-2133.2009.09574.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of TXNDC5 gene polymorphisms and susceptibility to nonsegmental vitiligo in the Korean population

Abstract: These results suggest that TXNDC5 gene polymorphisms are associated with the development of NSV in the Korean population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…TXNDC5 expression is induced by hypoxia (Sullivan et al., 2003), and variants in this gene have been associated with a number of autoimmune diseases, including rheumatoid arthritis (Chang et al., 2011) and vitiligo (Jeong et al., 2010). As for HDAC9, variants in TXNDC5 have not previously been associated with immune cell infiltration, again suggesting that iQTLs can uncover clinically relevant associations.…”
Section: Resultsmentioning
confidence: 99%
“…TXNDC5 expression is induced by hypoxia (Sullivan et al., 2003), and variants in this gene have been associated with a number of autoimmune diseases, including rheumatoid arthritis (Chang et al., 2011) and vitiligo (Jeong et al., 2010). As for HDAC9, variants in TXNDC5 have not previously been associated with immune cell infiltration, again suggesting that iQTLs can uncover clinically relevant associations.…”
Section: Resultsmentioning
confidence: 99%
“…They genotyped seven SNPs and found that three exonic SNPs (rs1043784, rs7764128 and rs8643) were statistically associated with NSV. The haplotypes AGG and GAA, consisting of rs1043784, rs7764128 and rs8643, demonstrated a significant association with NSV [18]. Lin et al reported that SNP rs13873 and haplotypes rs1225934 to rs13873 of BMP6-TXNDC5 genes were significantly associated with schizophrenia [19].…”
Section: Discussionmentioning
confidence: 99%
“…investigated the role of TXNDC5 in development of the skin disorder vitiligo [61]. A total of 230 Korean patients with non-segmental vitiligo were investigated for SNPs in the TXNDC5 gene; in total, seven SNPs were identified in the TXNDC5 gene, three of which (rs1043784, rs7764128, and rs8643) demonstrated an association with the vitiligo phenotype [61]. Although relevant in vivo studies have been conducted on the role of TXNDC5 no biochemical parameters have been evaluated, with regard to its role in disulfide bond oxidation and reduction.…”
Section: The Human Pdi Gene Familymentioning
confidence: 99%